DECISION-MAKING SKILL CHARACTERIZATION IN GLOBAL WARMING TOPICS USING PARTIAL CREDIT ANALYSIS MODEL - Raniah, Siti Fairuz (Jurnal Penelitian Pendidikan, 2019)
Decision making skill is an important aspect in education. In the process of learning, decision making skill is delivered in informal discussion, in the form of verbal expression. But, to increase students’ awarness of the sosio-science topic are needed measurements about the formal and written decision making process. This research aimed to measure the process of decision-making skill of the students in regard to global warming issue. The methods that used in this study is the construction and validation methods. A total of 107 XII-grade students was involved in this study to obtain the raw data. The obtained data then analyzed with Item Response Theory (IRT) with the model of Partial Credit Model (PCM). The data then was used to measure reliability, test characteristic curve, and test information function. The measured parameters were student’s skills in considering choice alternative criteria, choosing alternative decisions, and reflecting the decided option impact to themselves. Results showed that the decision-making process has a medium difficulty and has difference power in a good category. The reliability of the decision -making process is in the range of -2 to 2.3. The test was considered reliable and can be applied to either high or low level of ability students.